UN Food Systems Summit 2021: Dismantling Democracy and Resetting Corporate Control of Food Systems - Canfield, Matthew; Anderson, Molly D.; McMichael, Philip (Frontiers in Sustainable Food Systems, 2021)
This article analyzes the development and organization of the United Nations Food Systems Summit (UNFSS), which is being convened by UN Secretary General António Guterres in late 2021. Although few people will dispute that global food systems need transformation, it has become clear that the Summit is instead an effort by a powerful alliance of multinational corporations, philanthropies, and export-oriented countries to subvert multilateral institutions of food governance and capture the global narrative of “food systems transformation.” This article places the upcoming Summit in the context of previous world food summits and analyzes concerns that have been voiced by many within civil society. It elaborates how the current structure and forms of participant recruitment and public engagement lack basic transparency and accountability, fail to address significant conflicts of interest, and ignore human rights. As the COVID-19 pandemic illuminates the structural vulnerabilities of the neoliberal model of food systems and the consequences of climate change for food production, a high-level commitment to equitable and sustainable food systems is needed now more than ever. However, the authors suggest that the UNFSS instead seems to follow a trajectory in which efforts to govern global food systems in the public interest has been subverted to maintain colonial and corporate forms of control.